ANALISIS KEBUTUHAN MEDIA PODCAST DALAM MENINGKATKAN LITERASI DIGITAL MAHASISWA - Ade Aini Nuran; Feriyanti Elina Gultom; Puan Suri Mira Annisa (Program Studi Pendidikan Bahasa dan Sastra Indonesia, Fakultas Bahasa dan Seni, Universitas Negeri Medan, 2024)
Digital literacy is becoming a crucial skill for managing information effectively and credibly in the digital era. Podcasts, as an increasingly popular audio medium, have significant potential to enhance students' digital literacy. This study aims to analyze the need for podcasts as a medium to improve digital literacy among 20 English Education students through a qualitative case study. Data were collected through questionnaires and analyzed qualitatively. The results show that most respondents are familiar with podcasts and consider them important for digital literacy. Although the majority have never created a podcast, they expressed a need for training. Almost all respondents reported an increase in digital literacy after listening to educational podcasts. The main obstacles in podcast production include a lack of interest, technical knowledge, and limited resources. In conclusion, podcasts have significant potential to enhance students' digital literacy. Integrating podcasts into higher education can enrich the learning experience and develop critical skills in managing digital information. Further research is needed to measure the broader impact of podcasts and to develop integrated podcasts in higher education, as well as to provide training to improve podcast production quality. Comparative studies between types of podcast content and the long-term impact of podcasts on students' digital literacy and professional readiness are also necessary.